1997
DOI: 10.1007/bf02464368
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and turbeculostatic activity of podands with fluoroquinolone fragments

Abstract: Fluorine-substituted quinolonecarboxylic acids are known as synthetic antibacterial drugs with a broad spectrum of activity, which are successfully used for the therapy of various bacterial diseases, including tuberculosis [1 ]. Nevertheless, problems pertaining to the appearance of bacterial strains resistant to quinolones stimulate researchers to continue investigations aimed at a modification of the known fluroquinolones [2].We have attempted to modify a fluoroquinolone fragment responsible for penetration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 2 publications
0
4
0
2
Order By: Relevance
“…Another research study revealed that dimers of the same fluoroquinolones or two different fluoroquinolones linked by a linker at C‐7 exhibited highly promising antibacterial activity against tested bacterial strains . From the results, it is clear that derivatives with a bulky C‐7 side chain are more potent against efflux mutants .…”
Section: Recent Advances Of Quinolone Antibacterial Agentsmentioning
confidence: 99%
“…Another research study revealed that dimers of the same fluoroquinolones or two different fluoroquinolones linked by a linker at C‐7 exhibited highly promising antibacterial activity against tested bacterial strains . From the results, it is clear that derivatives with a bulky C‐7 side chain are more potent against efflux mutants .…”
Section: Recent Advances Of Quinolone Antibacterial Agentsmentioning
confidence: 99%
“…In order to improve the pharmacokinetic properties of fluoroquinolones, they were modified with aminoether or polyethyleneamine podand fragments, which are able to penetrate through cell membranes (Scheme 20) [60]. This modification gave derivatives 63 that proved to be specifically active against micobacteria under a low toxicity.…”
Section: Fluorinated Benzazinesmentioning
confidence: 99%
“…Many other biological pharmacophores such as azole/hydrozone , benzofuroxan , bisphosphonate , catecholate , citrate , glycoside , isoniazid , kanamycin , kojic acid , β ‐lactams , lactone , imidazole , sideromycins , peptide , phenothiazinium , pyochelin , pyoverdin , pyrazine , pyridyl , pyrimidine , pyrrazole , quinolone , sulfonamide , siderophore , tetrahydroquinoline , 1,3,4‐thiadiazol/oxadiazol , thiazole , triazine , and trifluoroacetimidoyl have been introduced into the piperazinyl subunit of FQs; although some of them such as lactone‐CPFX hybrid 23 (MIC of 0.11 μg/mL against multidrug‐resistant E . coli , which was 50 times more potent than the parent CPFX ) showed promising activity against Gram‐negative pathogens, the majority of them were less active than the parents.…”
Section: Structure–activity Relationshipmentioning
confidence: 99%